Aplikasi Business Intelligence Dashboard sebagai Alat Monitoring dan Bahan Pengambilan Keputusan Sales and Account Receivable - Putra, Fadil Muhammad; Sari, Risna (MULTINETICS, 2016)
Information and data are the important assets for a company. To process data into useful information and getting to be knowledge in the decision making process at management level, there are so many companies which have difficulties, including PT XYZ which was engaging in the production of agricultural materials. PT XYZ had the difficulties in monitoring process and decision-making process related to its main business, sales and account receivable. Business Intelligence dashboard could be the best solution to overcome these problems. This research discusses related design, construction and implementation of business intelligence solutions dashboard starting from the architecture business intelligence, data warehouse in form of a data mart, ETL (extraction, transformation, and loading) process are useful for generating the quality of data, and visualization in the form of dashboard that would represent key business process with XYZ company. The method used in the development of business intelligence dashboard refers to the six-step method of executive information system that is of the justification, planning, business analysis, design, construction, deployment that would generate digital dashboard for level management. The result is a website application consisting of three digital dashboards that become visualization tools to display the information and knowledge needed in the monitoring process and become material to produce decisions related to sales and receivables. The BI solutions that are developed are in line with expectations and can meet the business needs of PT XYZ.